ANTIOXIDANT ACTIVITY ON SARRABBA IS BASED ON THE PROPORTION OF RED GINGER EXTRACT (ZINGIBER OFFICINALE ROSCOE) AND CINNAMON EXTRACT (CINNAMOMUM VERUM J. PRESL) (Journal of Agriculture, 2023)
This study aims to evaluate the antioxidant activity, total phenol, yield and evaluation of the panelists' preference level including color, taste and aroma of instant sarabba. Sarabba is processed into an instant drink to extend the shelf life of the sarabba drink and is practical.  The research method used was a completely randomized design (CRD) method with 4 treatment levels of the proportions of red ginger extract and cinnamon extract namely A (100% : 0%), B (95% : 5%), C (90% : 10%) ) and D (85% :15%) with 3 repetitions. The analytical method used in this research is the Folin Chiocalteau method for the total phenol test, the DPPH (1,1-diphenyl, -2 picrylhydrazyl) method for the antioxidant activity test. The results showed that the IC50 of instant sarabba ranged from 662.13 - 886.93 ppm and total phenol ranged from 2.21 - 6.75 mgGAE/100 g sample. Treatment of the proportion of 100% red ginger extract and 0% cinnamon extract had the strongest antioxidant activity with IC50 of 662.13 ppm and total phenol with a value of 6.75 mgGAE/100 g simple